Pengaruh EWOM, Social Media Engagement, dan Brand Image terhadap Keputusan Pembelian Skincare Avoskin Melalui Shopee Oleh Generasi Z - Marisa Dwi Rahmawati; Siti Komariah Hildayanti; Fauziah Afriyani (Yayasan Lentera Avanya Nagari, 2026)
This study aims to analyze the influence of Electronic Word of Mouth (E-WOM), Social Media Engagement, and Brand Image on purchasing decisions for Avoskin skincare products through the Shopee e-commerce platform among Generation Z consumers. This research used a quantitative method by distributing online questionnaires to Generation Z consumers in Palembang who had purchased Avoskin products via Shopee. The sampling technique applied was purposive sampling, with a total of 97 respondents. Data were analyzed using multiple linear regression through SPSS version 27. The findings indicate that Electronic Word of Mouth, Social Media Engagement, and Brand Image have positive and significant effects on purchasing decisions. Among these variables, Brand Image provides the strongest contribution in influencing consumer decisions. Furthermore, all independent variables simultaneously have a significant influence on purchasing decisions. These results demonstrate that consumer purchasing decisions are strongly affected by digital communication, social media involvement, and positive brand perceptions formed in consumers’ minds during the purchasing process. The study confirms that Electronic Word of Mouth and Brand Image are dominant factors influencing Generation Z consumers in purchasing Avoskin skincare products through Shopee. The findings also highlight the importance of maintaining effective digital marketing strategies to strengthen consumer trust continuously online.